1990
DOI: 10.1103/physrevb.41.12895
|View full text |Cite
|
Sign up to set email alerts
|

X-ray-diffraction studies of hydration transitions in Na vermiculite

Abstract: Hydration phase transitions in Na vermiculite, a specific example of expandable 2:1 layered silicates, were examined as a function of temperature at a constant water-vapor pressure by x-ray diffraction. The samples exhibited well-defined 0-, 1-, and 2-water-layer hydration states (WLHS s) with the basal spacings of 9.81, 11. 84, and 14.89 A, respectively. The transitions between the hydration states were found to be first order, evidenced by a two-phase coexistence and large hysteresis.Substantial elastic defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…Hydration of individual clay particles, in particular, occurs through the intercalation of water molecules in the space between adjacent silica platelets, inside the stacks. The stepwise swelling of the nanostacks resulting from molecular packing between clay platelets (Skipper et al, 1991), is a well known first order transition between hydration states corresponding to up to four 'water layers' (Suzuki et al, 1987;Wada et al, 1990; da Silva et al, 2002). The thermodynamically stable state is controlled by the ambient temperature (T) and humidity (H) with transitions occurring along given (H, T) lines (Wada et al, 1990;da Silva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydration of individual clay particles, in particular, occurs through the intercalation of water molecules in the space between adjacent silica platelets, inside the stacks. The stepwise swelling of the nanostacks resulting from molecular packing between clay platelets (Skipper et al, 1991), is a well known first order transition between hydration states corresponding to up to four 'water layers' (Suzuki et al, 1987;Wada et al, 1990; da Silva et al, 2002). The thermodynamically stable state is controlled by the ambient temperature (T) and humidity (H) with transitions occurring along given (H, T) lines (Wada et al, 1990;da Silva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The stepwise swelling of the nanostacks resulting from molecular packing between clay platelets (Skipper et al, 1991), is a well known first order transition between hydration states corresponding to up to four 'water layers' (Suzuki et al, 1987;Wada et al, 1990; da Silva et al, 2002). The thermodynamically stable state is controlled by the ambient temperature (T) and humidity (H) with transitions occurring along given (H, T) lines (Wada et al, 1990;da Silva et al, 2003). For Na fluorohectorite and at H ' 100%, for example, the system goes from zero water layers (WL) up to two WL between 393 and 275 K (da Silva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we observe a temperature hysteresis of at most about 5"C. By contrast, an x-ray diffraction study of Na vermiculite has revealed a much larger hysteresis of about 26°C in temperature cycling: the zero-water-layer peak appeared at 58°C upon heating, and persisted to 32°C on subsequent cooling (at a water vapor pressure of % 20 torr) [5]. However, the notable difference between the two studies is that for the Na vermiculite experiment, the system was allowed to stabilize for 6-12 hours at each temperature.…”
Section: Discussionmentioning
confidence: 96%
“…1, dot-dash line). And as with other swelling clays [5], the temperatures at which the various hydration states may be found is variable, dependent on the sample environment and history.…”
Section: Resultsmentioning
confidence: 99%
“…47 However, one of the most studied, although not yet completely understood complex system, is the 48 interaction between water and the clay mineral. The process of water intercalation is highly 49 dependent on the interlayer cation as well as on the layer charge (Dazas et al, 2013;Gates, 2006; 50 Gates et al, 2012) and it has been studied by many techniques such as X-ray diffraction (XRD) 51 (Wada et al, 1990), X-ray absorption fine structure (XAFS) (Ashley and Doniach, 1975; Lee and 52 Beni, 1977; Lee and Pendry, 1975;Schaich, 1973), nuclear magnetic resonance (NMR) (Tenorio et 53 al., 2010(Tenorio et 53 al., , 2008 and Quasi-elastic Neutron Scattering (QENS) (Bordallo et al, 2008;Gates et al, 54 2012). 55…”
Section: Introduction 40mentioning
confidence: 99%